An assessment of the maxilla after rapid maxillary expansion using cone beam computed tomography in growing children - Jessica L. Woller; Ki Beom Kim; Rolf G. Behrents; Peter H. Buschang (Dental Press Editora, 2014)
INTRODUCTION: With the advent of cone beam computed tomography (CBCT), it is now possible to quantitatively evaluate the effects of rapid maxillary expansion (RME) on the entire maxillary complex in growing patients. OBJECTIVE: The purpose of this study is to use three-dimensional images to evaluate the displacement that occurs at the circummaxillary sutures (frontonasal, zygomaticomaxillary, intermaxillary, midpalatal, and transpalatal sutures) following rapid maxillary expansion in growing children. METHODS: The CBCT scans of 25 consecutively treated RME patients (10 male, 15 female) with mean age of 12.3 ± 2.6 years, were examined before expansion and immediately following the last activation of the expansion appliance. RESULTS: Statistically significant (P < 0.05) amounts of separation were found for the displacement of the bones of the frontonasal suture, the intermaxillary suture, the zygomaticomaxillary sutures, and the midpalatal suture. The change in angulation of the maxillary first molars due to RME was also statistically significant. There was no statistically significant displacement of the transpalatal suture. CONCLUSIONS: Rapid maxillary expansion results in significant displacement of the bones of circummaxillary sutures in growing children.